Presentation and Management of Hepatic Injury due to Blunt Trauma in Patients Attending in Casualty Block of dmch- a Study of 50 cases (Journal of Dhaka Medical College, 2017)
Objective: To diagnose the cases of hepatic injury due to blunt abdominal trauma in a shortest possible time and find out the way of efficient and planned management of hepatic injury in our present setting.Materials and methods: This study was done in the casualty department of Dhaka Medical College Hospital and 50 patients of hepatic injury following blunt abdominal trauma were selected over a period of January 2010 to December 2010. All 50 patients were admitted within 24 hours of incidence. The patients were diagnosed clinically by history and physical examination and relevant investigations. Immediately after admission patients were resuscitated by clearance of airway, maintenance of respiration, arrest of external bleeding and maintenance of normal circulation (ATLS Protocol). After resuscitation further management was planned depending upon the condition of the patient. Clinical presentation, overall management and outcome were evaluated by the available resources of casualty ward of DMCH.Results: Most patients were male (88%) and 68% of patients were belonged to age group of 21 to 40 years. Most of the patients (90%) were injured as a result of road traffic accidents. All patients had a history of trauma and most of them presented with abdominal pain, tenderness muscular rigidity of abdomen and shock (38%). Only 13 (26%) patients had isolated hepatic injury. Rest of the patients had associated other organ injuries. Majority patients (46%) had Grade-I hepatic injury. Out of 50 patients, 46 were operated and most of them had other intra abdominal organ injuries and 4 patients were given non-operative management. Suture hepatorrhaphy was done in 38 (76%) cases. Most common post operative complications were pulmonary in origin (24%) and three patients were died in this series.Conclusion: Simple technique of hemostasis such as suture hepatorrhaphy is sufficient in most cases with adequate drainage and non operative management can be tried based on haemodynamic stability.J Dhaka Medical College, Vol. 25, No.2, October, 2016, Page 133-137